2016
DOI: 10.3389/fphar.2016.00469
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Herbal Medicine on Cardiovascular Diseases and the Mechanisms of Action

Abstract: Cardiovascular diseases are the principal cause of death worldwide. The potentially serious adverse effects of therapeutic drugs lead to growing awareness of the role of Chinese herbal medicine in the treatment of cardiovascular diseases. Chinese herbal medicine has been widely used in many countries especially in China from antiquity; however, the mechanisms by which herbal medicine acts in the prevention and treatment of cardiovascular diseases are far from clear. In this review, we briefly describe the char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(70 citation statements)
references
References 113 publications
0
63
0
Order By: Relevance
“…Crataegus spp. were also reviewed together with other botanicals (Chen et al, 2009;Schmitt and Dirsch, 2009;Rastogi et al, 2016;Dennehy, 2001;Bjorklund et al, 2018), Chinese Traditional Medicine plants (Xie et al, 2012;Liu and Huang, 2016;, various herbal products (Ahmad et al, 2013;Nunes et al, 2017), nutraceuticals (Houston, 2005) and natural antioxidants (Zhao, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Crataegus spp. were also reviewed together with other botanicals (Chen et al, 2009;Schmitt and Dirsch, 2009;Rastogi et al, 2016;Dennehy, 2001;Bjorklund et al, 2018), Chinese Traditional Medicine plants (Xie et al, 2012;Liu and Huang, 2016;, various herbal products (Ahmad et al, 2013;Nunes et al, 2017), nutraceuticals (Houston, 2005) and natural antioxidants (Zhao, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Based on the principle of holistic regulation and syndrome differentiation and treatment, CHMs have been widely used in disease prevention and treatment in China and have been proven to have great clinical effectiveness on cardiovascular system disease. A previous study that summarized and introduced the application of plant products in CHD, AS, dyslipidemia, and hypertension also sorted formulae and herbs according to specific cardiovascular diseases [7]. e plant products applied in AS and dyslipidemia Over the last decades, some TCM decoctions have been confirmed to be effective in the treatment of CHD.…”
Section: The Therapeutic Effect Of Tcm In Chdmentioning
confidence: 99%
“…According to new studies, the pharmacological mechanisms of CHM are relevant to the effects on vascular smooth muscle cells (VSMCs), endothelial cells, cardiomyocytes, macrophages, and monocytes. Details are shown in Table 2 [7].…”
Section: The Therapeutic Effect Of Tcm In Chdmentioning
confidence: 99%
“…Endothelial factors that are most commonly held to account for the actions of vasodilator drugs, which may also explain the actions of vasodilator medicinal plants ( Vasorelaxants which act through interference with Ca 2+ influx via VOCC or ROCC are usually differentiated using relaxation responses of isolated arterial rings precontracted with high K + (VOCC) or phenylephrine (ROCC). 22 Some studies have reported that medicinal plants may induce vasodilation by inhibiting Ca 2+ influx, as well as the release from intracellular stores. 23 In rat mesenteric arteries, baicalin, a flavonoid compound isolated from Scutellaria baicalensis 22 was shown to significantly reduced the increase in Ca 2+ induced by stimulation with Angiotensin II, vasopressin and endothelin, by a mechanism linked with inhibition of lipoxygenase biosynthesis and release of vasoconstrictor prostaglandins.…”
Section: Vascular Endotheliummentioning
confidence: 99%